2010
DOI: 10.1007/s00345-010-0578-7
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of periprostatic local anaesthetic infiltration in transrectal ultrasound biopsy of prostate: a prospective randomised control study

Abstract: We suggest that a 10 cc 1% Lignocaine infiltration at the apical region of the prostate be used to obtain best pain relief during this procedure. Plain lubricant jelly is sufficient for probe insertion. There is no need to alter the anaesthetic requirement if number of cores is increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…1). After screening 46 RCTs15678910111213141516171819202122232425262728293031323334353637383940414243444546474849 met our study criteria and were included in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…1). After screening 46 RCTs15678910111213141516171819202122232425262728293031323334353637383940414243444546474849 met our study criteria and were included in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…They highlighted that no additional anesthesia was needed despite the increased number of core biopsies. 22 Hossack and Woo injected 2.5-mL 2% lignocaine into the periprostatic area before the TRUS-guided biopsy in their study. They reported that the patients tolerated the procedure very well, and 97.5% of the patients stated that they would accept this method again if another PBx was required.…”
Section: Resultsmentioning
confidence: 98%
“…This was supported by a study involving 386 men, who were randomized to receive no anesthetic, 10 ml of 1% lidocaine at the apical region of the prostate, 5 ml of 1% lidocaine at the bases of the prostate bilaterally, and lastly 4 ml at the apex and 3 ml at the bases bilaterally of 1% lidocaine. 56 The authors found that 10 ml of apical local anesthetic had the most superior pain relief. However, other studies have not supported this finding.…”
Section: Peri-prostatic Nerve Blockmentioning
confidence: 99%
“…18 Since then many studies have advocated for more apical injections. 55,56 The neurovascular bundles run postero-lateral to the prostate gland between the capsule and Denovilllier's fascia and pierce the capsule at the base and apically at the 4 and 8 o'clock location. It has been suggested that injection at these locations will numb the whole gland.…”
Section: Peri-prostatic Nerve Blockmentioning
confidence: 99%